Tunable hydrocarbon adsorption based on a zeolitic imidazolate framework in the sodalite topology - Falkowski, Joseph M; Ravikovitch, Peter I; Abdulkarim, Mary S; Muraro, Giovanni M; Liu, Sophie F; Paur, Charanjit; Strohmaier, Elisa A; Weston, Simon C (Journal of materials chemistry. A, Materials for energy and sustainability, 2022)
Manipulation of materials exhibiting step-shaped isotherms using simple and scalable methods is key to realizing their utility in advanced separation schemes. To this end, we have discovered EMM-36, a hybrid isostructural to ZIF-7 material in the sodalite topology prepared from industrially scalable organic moieties. Through simple compositional tuning of EMM-36 that remains true to the linker composition introduced in the synthesis, controlled manipulation of the step-function adsorption behaviour of gases onto the flexible framework has been realized. We observe that the energetics for the phase transformation from a denser narrow pore (np) to more open large pore (lp) phase are directly controllable while maintaining the hexagonal crystal structure characteristic of the lp phase of ZIF-7 under adsorbed conditions throughout the entire hybrid compositional range. The structural flexibility of ZIF-7 is controlled via a mixed-linker approach resulting in modified adsorption properties tunable across 2 orders of magnitude of step pressure while maintaining the ZIF-7 structure throughout the compositional range.